AAV8-mediated overexpression of mPCSK9 in liver differs between male and female mice. (November 2018) - Vozenilek, Aimee E.; Blackburn, Cassidy M.R.; Schilke, Robert M.; Chandran, Sunitha; Castore, Reneau; Klein, Ronald L.; Woolard, Matthew D.
Abstrat: Background and aims: The recombinant adeno-associated viral vector serotype 8 expressing the gain-of-function mutation of mouse proprotein convertase subtilisin/kexin type 9 (AAV8- PCSK9) is a new model for the induction of hypercholesterolemia. AAV8 preferentially infects hepatocytes and the incorporated liver-specific promoter should ensure expression of PCSK9 in the liver. Since tissue distribution of AAVs can differ between male and female mice, we investigated the differences in PCSK9 expression and hypercholesterolemia development between male and female mice using the AAV8-PCSK9 model. Methods: Male and female C57BL/6 mice were injected with either a low-dose or high-dose of AAV8-PCSK9 and fed a high-fat diet. Plasma lipid levels were evaluated as a measure of the induction of hypercholesterolemia. Results: Injection of mice with low dose AAV8-PCSK9 dramatically elevated both serum PCSK9 and cholesterol levels in male but not female mice. Increasing the dose of AAV8-PCSK9 threefold in female mice rescued the hypercholesterolemia phenotype but did not result in full restoration of AAV8-PCSK9 transduction of livers in female mice compared to the low-dose male mice. Our data demonstrate female mice respond differently to AAV8-PCSK9 injection compared to male mice. Conclusions: These differences do not hinder the use of female mice when AAV8-PCSK9 doses are taken into consideration. However, localization to and production of AAV8-PCSK9 in organs besides the liver in mice may introduce confounding factors into studies and should be considered during experimental design. Highlights: Hypercholesterolemia differs between male and female mice in response to AAV8-PCSK9 AAV8-PCSK9 transduction of female mice is less effective High-dose AAV8-PCSK9 injection results in PCSK9 mRNA in tissues besides the liver